2021
DOI: 10.12737/stp-73202104
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and diagnostic potential of the ionospheric Alfvén resonator

Abstract: The layering of the ionosphere leads to the formation of resonators and waveguides of various kinds. One of the most well-known is the ionospheric Alfvén resonator (IAR) whose radiation can be observed both on Earth’s surface and in space in the form of a fan-shaped set of discrete spectral bands (DSB), the frequency of which changes smoothly during the day. The bands are formed by Alfvén waves trapped between the lower part of the ionosphere and the altitude profile bending of Alfvén velocity in the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These boundaries, which are located above the F‐region peak and toward the bottom of the ionosphere, cause the Alfvén velocity gradient to reach a maximum. This process sets up a resonance in the ionospheric cavity centered on the F‐region, which was first proposed by Polyakov (1976). Several mechanisms for the production of IAR have been considered, including the ionospheric feedback instability at higher latitudes (Lysak, 1991).…”
Section: Introductionmentioning
confidence: 82%
“…These boundaries, which are located above the F‐region peak and toward the bottom of the ionosphere, cause the Alfvén velocity gradient to reach a maximum. This process sets up a resonance in the ionospheric cavity centered on the F‐region, which was first proposed by Polyakov (1976). Several mechanisms for the production of IAR have been considered, including the ionospheric feedback instability at higher latitudes (Lysak, 1991).…”
Section: Introductionmentioning
confidence: 82%
“…The upper boundary is likely to be above the F region peak, and the lower boundary is toward the bottom of the ionosphere, where the Alfvén velocity maximizes. The resonance which occurs is termed the Ionospheric Alfvén Resonator (IAR) (Polyakov, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The upper boundary is likely to be above the F region peak, and the lower boundary is toward the bottom of the ionosphere, where the Alfvén velocity maximizes. The resonance which occurs is termed the Ionospheric Alfvén Resonator (IAR) (Polyakov, 1976).The first confirmed observation of IAR was at mid-latitudes (Belyaev et al, 1989), and since then IAR have been observed in magnetometer data across a range of latitudes. They have also been observed in sounding rocket (…”
mentioning
confidence: 98%